Perubahan Stratifikasi Sosial Masyarakat Bugis di Kabupaten Bone (Dalam Perspektif Pendidikan) - Widya Karmilasari (Paedagogik, 2013)
Social stratification is a class or order system in a comnvunity. Buginese people have been long familiar with the so called "stratification" as it is found the manuscript of La Galigo. Kabupaten Bone itself which was one the largest kingdom in South Sulawesi acknowledges the existence of social stratification among the people in which they were classified into high class, middle class, and lower class. However it is assumed that the increase of the education level of the people becomes one important indicator of the change of the social stratification in the society. This study is descriptive-qualitative in nature. The population is taken from three "kecainatan " or sub-districts contiguous g-uous to Watampone is the main town in this "kabupaten. The three "kecatnatan" was also known in the kingdom era as Lalebata area. The data -was obtained through in-dept interview, observation, and information from several informants. Keyword: Social stratification, Buginese people